2011
DOI: 10.1007/s11046-011-9498-3
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Intensive Care Unit Candidemia: Epidemiology, Risk Factors, Outcome, and Critical Review of Published Case Series

Abstract: Evaluation of epidemiological trends, risk factors, and clinical outcome associated with candidemia at a neonatal intensive care unit is reported. From January 2005 to December 2009, forty candidemia cases were identified. C. albicans and C. parapsilosis were the most common species recovered (69 and 24%, respectively). All C. parapsilosis strains were susceptible to antifungals, whereas, C. albicans exhibited higher resistance rates to azoles. Low birth weight, low gestational age, presence of central lines, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
2
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 38 publications
4
25
2
5
Order By: Relevance
“…Historically, C. albicans has been the leading cause of invasive fungal infections; however the frequency of infections caused by non -albicans species has dramatically increased [35]. Numerous studies have reported that infections caused by C. parapsilosis account for 15–67% of invasive candidiasis in premature newborn infants, and in some centers this species surpasses C. albicans as the predominant cause of neonatal candidiasis [6]. Interestingly, C. parapsilosis is often associated with lower mortality rates in the human host and is significantly less virulent than C. albicans in mouse models of infections [712].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, C. albicans has been the leading cause of invasive fungal infections; however the frequency of infections caused by non -albicans species has dramatically increased [35]. Numerous studies have reported that infections caused by C. parapsilosis account for 15–67% of invasive candidiasis in premature newborn infants, and in some centers this species surpasses C. albicans as the predominant cause of neonatal candidiasis [6]. Interestingly, C. parapsilosis is often associated with lower mortality rates in the human host and is significantly less virulent than C. albicans in mouse models of infections [712].…”
Section: Introductionmentioning
confidence: 99%
“…Despite improvements in antifungal prevention and treatment that came with the discovery of newer azoles and echinocandins, invasive candidiasis (IC)/candidaemia are related with high mortality rates, ranging from 36% to 63% in different studies and patients groups . For paediatric patients, fewer epidemiological data exist but mortality rates range from 7.7–26% to as high as 43–54% among neonates or infants …”
Section: Introductionmentioning
confidence: 99%
“…Currently, Candida parapsilosis has been recognized as the second or third most frequently isolated Candida species that causes bloodstream infection (2,3,4). C. parapsilosis infections particularly affect neonates (5,6) and surgical intensive care unit (ICU) patients (7). C. parapsilosis is often found on the hands of health care workers, which is associated with outbreak infections (7,8).…”
mentioning
confidence: 99%